Pengurangan Ketidakpastian Dalam Komunikasi Antar Budaya Pada Masyarakat Suku Anak Dalam Dengan Masyarakat Jawa Di Desa Q1 Tambah Asri Musi Rawas - Sopiyan, Wawan (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2024)
In South Sumatra, the Anak Dalam Tribe community inhabits forests that are included in the administrative areas of Musi Rawas Regency and North Musi Rawas Regency. In the village of Q1 Tambah Asri, the Anak Dalam Tribe community lives and interacts with the Javanese community. The purpose of this study was to determine how to reduce uncertainty in intercultural communication between the Anak Dalam Tribe community and the Javanese community in Q1 Tambah Asri Village, Tugumulyo District, Musi Rawas Regency. In this study, the researcher used the Descriptive Qualitative Method. The findings of this study are that the majority of the Anak Dalam Tribe community who have settled initially closed themselves off from interaction with the Javanese community because they experienced uncertainty in communication. Gradually, over time, by starting communication, interactions occurred that eroded uncertainty in communication in the Anak Dalam Tribe community. The conclusion of this study is that communication is a tool to reduce uncertainty in intercultural communication between the Anak Dalam Tribe community and the Javanese community in Q1 Tambah Asri Village, Tugumulyo District, Musi Rawas Regency, South Sumatra.